PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Licoprsicon esculentum Mill)PADA BERBAGAI JARAK TANAM DAN PEMANGKASAN - St. Sabahannur St. Sabahannur; Lingga Herawati (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2017)
The airs of the study was to determine the effect of plant spacing and pruning on the growth and production of tomato plants. The research was conducted in the form of Randomized Block Design consisting of 2 Factorials. The first factor is plant spacing consisting of three levels: 70cm x 50cm, 60cm x 50cm and 40cm x50 cm. The second factor of pruning consists of 3 levels: not trimmed (control), trimmed and leaving two branches and trimmed and leaving three branches. The parameters observed were: number of leaves, flowering age, fruit crop weight and production per hectare. The results showed that plant spacing and pruning significantly affected the weight of fruit per plant, and production per hectare, but no significant effect on the number of leaves, and the age of flowering, and the interaction only had significant effect on flowering age. Spacing of 40cm x 50cm produces a higher production of 22.83 tons per hectare. Treatment of pruning by leaving three main branches produces the best crop production of 23.31 tons per hectare. Planting distance of 60cm x 50cm and pruning which leaves three branches produces flowering age of 19.67 days.